Potential ecological risk and accumulation of heavy metal(loid)s in soils of Macao in China as a non-industrial and tourist City - Yao Ma; Boran Shao; Wenjun Li; Ying Li; Yang Wu; Ni Xiong; Bingzheng Zhou; Yibing Ma (Scientific Reports)
Abstract With rapid industrialization, the accumulation and contamination of heavy metal(loid)s in soil often has occurred. However, the accumulation of heavy metal(loid)s in soil in non-industrial and tourist cities with high population densities is not well known. Therefore, the Macao Special Administrative Region (Macao SAR) was taken as an example to investigate the spatial and temporal changes in the characteristics of soil heavy metal(loid)s in non-industrial and tourist cities. The total concentrations of heavy metal(loid)s (As, Co, Cd, Cr, Cu, Pb, Ni, Hg, and Zn) in soil as well as the ecological risk in different functional areas and geographic locations were studied by combining statistical analysis, the land accumulation index, and the potential ecological risk index. Finally, the data in 2018 and 2023 were compared. The results show that in terms of spatial distribution, the high CVs (coefficients of variation) of 0.67 and 0.73 for Cr and Hg, respectively, showed Cr and Hg were more likely to have point sources of contamination. The skewness value of 0.16 for Zn suggests that the distribution may be slightly skewed and flat, with a more uniform distribution, probably due to the high-density distribution of the population and atmospheric deposition. Compared with other areas, heavy metal(loid) concentrations in soils were generally higher in the Macao Peninsula, which may be related to the higher population of waste incineration plants and residential areas located there. Geographically, Hg concentrations in soils were higher near the airport and transportation areas than in other areas. From 2018 to 2023, heavy metal(loid)s (except Zn) in the soils of Macao did not increase significantly but showed a decreasing trend due to tourism-oriented activities, high rainfall, the absence of industry, and the COVID-19 pandemic. Cr, Cd, Zn, and Hg occur more frequently in the lower concentration ranges than the other heavy metal(loid)s and generally show decreasing trends. Although the potential ecological risk of heavy metal(loid)s in Macao was generally low, As had the highest potential risk. Most of the lightly contaminated sites (62%) had a higher geo-accumulation index of Zn than for the other heavy metal(loid)s. This paper can be used as the data support for future research on soil heavy metal(loid) distribution and government policies for non-industrial cities.